Antioxidant Capacity through Electrochemical Methods and Chemical Composition of Oenocarpus bataua and Gustavia macarenensis from the Ecuadorian Amazon - Carlos Méndez-Durazno; Pablo A. Cisneros-Perez; Bryan A. Loja-Ojeda; Raúl Monge-Sevilla; David Romero-Estévez; Lenys Fernández; Patricio J. Espinoza-Montero (Antioxidants, 2023)
This study evaluated the antioxidant properties and chemical composition of the seeds, pulp and peels of Ungurahua (Oenocarpus bataua) and Pasu (Gustavia macarenensis)—fruits, native to the Ecuadorian Amazon. The antioxidant capacity was measured by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and cyclic voltammetry (antioxidant index 50 (AI50)) assays; differential pulse voltammetry was used to evaluate antioxidant power using the electrochemical index. The total phenolic content, as well as the yellow flavonoid and anthocyanin content, were quantified via spectrophotometry. In addition, the trans-resveratrol and ascorbic acid content were evaluated through high performance liquid chromatography (HPLC). Ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) was used to identify secondary metabolites with possible therapeutic properties. Results showed that the Pasu peel and seed extracts had the highest antioxidant capacity, followed by the Ungurahua peel; these results were consistent for both spectroscopic and electrochemical assays. HPLC and UPLC-MS analysis suggest that Oenocarpus bataua and Gustavia macarenensis are important sources of beneficial bioactive compounds.